Expanded and Sustained Uptake of the Accelerated Breeding Scheme (ABS) Approach - International Potato Center (2016)
A major milestone in sweetpotato breeding progress was achieved in 2016, with the release of the second cycle of varieties bred in Mozambique using the Accelerated Breeding Scheme (ABS) approach.